The Legal Aspects and Challenges of Managing Workplace Mobbing - Bányai, Gábor; Boruzs, Klára; Bíró, Klára (International Journal of Engineering and Management Sciences, 2016)
Workplace mobbing (psychological harassment) can be a great challenge for the management of any organization. Although the phenomenon has been discovered for quite some time, there is still no unequivocal definition, and therefore preventive and managerial actions are rudimentary. It is clear that mobbing affects not only on the individual employee, but the whole organization. The reduction of commitment of people working in this environment (and not only those directly affected by it) may have a detrimental effect on the performance of the organization. I will present a legal case study to highlight some of the general and procedural shortcomings of mobbing at the workplace.